Upaya Peningkatan Imunitas Anak Karyawan Universitas Muhammadiyah Palembang dengan Vaksinasi Influenza - Chairani, Liza; Purwoko, Mitayani; Wakilla, Putri (Pusat Penelitian & Pengabdian Masyarakat Poltekkes Kemenkes Palu, 2023)
Influenza is a highly contagious respiratory tract disease, caused by several influenza RNA viruses. The Influenza vaccine shows a protective effect against the virus that causes COVID-19. The purpose of this activity was to increase parents' knowledge about influenza and increase children's immunity to the influenza virus. The form of activity was divided into two, namely health counseling to the parents and then followed by injecting the Influenza vaccine to the children. The health education method chosen was counseling in big class at Family Medicine Clinic, Faculty of Medicine, Universitas Muhammadiyah Palembang. Health education was preceded by a pre-test with 5 multiple choice questions and ended with a same-question post-test. The average pre-test score was 75.5 and the post-test score was 93.3. There was an increase in the score which indicates an increase in the knowledge of the parents. Of the 18 parents who attended counseling, only 6 parents allowed their children to be vaccinated. The number of children vaccinated was 11 people. The follow up showed no sign of adverse effects of Influenza vaccination on children.